1970
DOI: 10.1017/s0043174500034585
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diquat on Uptake of Copper in Aquatic Plants

Abstract: Combinations of copper sulfate pentahydrate (hereinafter referred to as CSP) at 1.0 ppmw copper plus 0.1 to 2.0 ppmw 6,7-dihydrodipyrido-(1,2-a:2′,1′-c)pyrazinediium ion (diquat) resulted in higher accumulations of copper in hydrilla (Hydrilla verticillata Casp.), egeria (Egeria densa Planch.), and southern naiad (Najas guadalupensis Spreng. Magnus) when compared to plants which received only CSP. A contact period greater than 24 hr was necessary before the higher amounts of copper were detected in those plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

1971
1971
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…These authors demonstrated that hydrilla treated with 1 ppmw of diquat plus 2 ppmw copper ion absorbed 176% more diquat than plants treated with 1 ppmw of diquat alone. In other studies it was found that hydrilla treated with 1 ppmw of both copper and diquat contained as much as 1,712 ppmw more copper than plants treated with copper alone (9). One significant aspect of the former study was the finding that the uptake of diquat by hydrilla was not enhanced until the level of copper ion in solu-tion reached approximately 0.5 ppmw.…”
Section: Introductionmentioning
confidence: 85%
“…These authors demonstrated that hydrilla treated with 1 ppmw of diquat plus 2 ppmw copper ion absorbed 176% more diquat than plants treated with 1 ppmw of diquat alone. In other studies it was found that hydrilla treated with 1 ppmw of both copper and diquat contained as much as 1,712 ppmw more copper than plants treated with copper alone (9). One significant aspect of the former study was the finding that the uptake of diquat by hydrilla was not enhanced until the level of copper ion in solu-tion reached approximately 0.5 ppmw.…”
Section: Introductionmentioning
confidence: 85%
“…Hydrilla was cultured and treated in a controlled environment as described by Sutton, Weldon & Blackburn (1970). In this study sodium bicarbonate was added to the nutrient solution at a concentration of 50 ppmw bicarbonate at the beginning ofthe growth period, except in the 4-day treatment with CSP at 0-25-16-0 ppmw of copper.…”
Section: Methodsmentioning
confidence: 99%
“…Hydrilla was cultured in a controlled environment and treated with herbicides as described by Sutton et al (1970). In this study sodium bicarbonate was added to the nutrient solution at a concentration of 50 ppmw of bicarbonate at the beginning of the growth period.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies (Sutton, Weldon & Blackburn, 1970) have shown that more copper was present in hydrilla, egeria {Egeria densa Planch.) and southern naiad {JVajas guadalupensis Spreng.…”
Section: Introductionmentioning
confidence: 99%